Congenital mandibular epulis – A rare oral lesion in a newborn - Abdul Rahman, Nurhani Yasmin; Ismail, Hashimah; Mohamad, Irfan; Yusof, Suhaimi; Mohamad, Hazama (Elsevier, 2015)
Introduction: Congenital epulis or congenital granular cell tumour is a rare benign lesion arising from alveolar mucosa of neonates which can cause respiratory and feeding problems. It is also known as Neumann’s tumour. Females are affected 10 times more frequent. Method: A review of medical record was performed. Result: A newborn presented with lesion over left lower gum which was seen during antenatal abdominal ultrasonography scan by Obstetrics team at 35-week of gestation. The case was referred for ex utero intrapartum treatment procedure in view of anticipating upper airway obstruction. Upon delivery via Caesarean section, patient had no obstructive symptoms however was immediately intubated few hours of life to secure airway. Computed tomography scan confirmed a soft tissue mass arising from either lower alveolus or tip of tongue. The lesion was excised and histopathological examination reported as congenital epulis. Conclusion: Even though it is a rare case, congenital epulis should be considered as one of differential diagnosis of an oral mass. A multi-disciplinary team management is important in view of possibility of upper airway obstruction post delivery.